IPO Auctions: English, Dutch, … French, and Internet - Biais, Bruno; Faugeron-Crouzet, Anne Marie (Journal of Financial Intermediation, 2002)
Unseasoned shares are sold through the Book Building process in the United States and the United Kingdom, fixed price offerings in several countries, uniform price auctions in Israel or the new internet-based Open IPO mechanism, and an auction-like mechanism called the Mise en Vente in France. We analyze and compare the performance of these various IPO mechanisms within the context of a unified theoretical model. Fixed price offerings lead to inefficient pricing and winner's curse. Dutch auctions can also lead to inefficiencies, to the extent that they are conducive to tacit collusion by investors. The Book Building and Mise en Vente can lead to optimal information elicitation and price discovery. We document empirically the similarity between the Book Building and the Mise en Vente. We discuss the implications of our analysis for the design of optimal Internet IPO auctions. Journal of Economic Literature Classification Numbers: G24, G3, D82.